O sentido da psicoterapia online para psicólogos - Oliveira, Yanco Paternó de (2022)
The use of technology is a growing issue in contemporary times and more and more technological innovations enter the daily lives of the population. In this context, the internet is a reality that is present in more than half of the households in Brazil and with the pandemic period there has been an increase in the use of online tools to perform psychotherapy. However, there is a need for studies on the subject, in view of the limited academic production on the subject and the limitation in answering about the scope and limits of this professional practice in the psychological area. Thus, the objective of this investigation was to understand the meanings and meanings of this practice for professionals working in the area, also seeking to identify which demands brought by patients in this context and which and how are the interventions carried out by psychologists. The methodology was qualitative, exploratory field research, analyzing the manifestation of the phenomenon through the bias of professionals who work remotely. The instruments used were semi-structured interviews carried out with six psychologists who have been working with the practice of psychotherapy for at least 5 years and online for at least one year. Data analyzes were performed using phenomenology. From the results achieved, it became evident that the meaning of online psychotherapy is a way of adapting the practice of care, which, at the same time as it builds new possibilities of understanding and meaning, through the incorporation of information technology to the psychologist's corporeality, the possibility of mutual access between the patient's and the psychologist's fields is lost. It was also found that there is a plurality of demands within the online office, as well as the possibility of a plurality of practices and theories. Finally, the lack of body and the difficulty of building and maintaining the therapeutic setting are problems that need more attention and research to be overcome.(AU)